Distinct Housing Conditions Reveal a Major Impact of Adaptive Immunity on the Course of Obesity-Induced Type 2 Diabetes - Sbierski-Kind, Julia; Kath, Jonas; Brachs, Sebastian; Streitz, Mathias; von Herrath, Matthias G.; Kühl, Anja A.; Schmidt-Bleek, Katharina; Mai, Knut; Spranger, Joachim; Volk, Hans-Dieter (Frontiers in Immunology, 2018)
Obesity is associated with adipose tissue inflammation, insulin resistance and the development of type 2 diabetes. However, our knowledge is mostly based on conventional murine models and promising pre-clinical studies rarely translated into successful therapies. There is a growing awareness of the limitations of studies in laboratory mice, housed in abnormally hygienic specific pathogen-free (SPF) conditions, as relevant aspects of the human immune system remain unappreciated. Here, we assessed the impact of housing conditions on adaptive immunity and metabolic disease processes during high-fat diet. We therefore compared diet-induced obesity in SPF mice with those housed in non-SPF, so called “antigen exposed” (AE) conditions. Surprisingly, AE mice fed a high-fat diet maintained increased insulin levels to compensate for insulin resistance, which was reflected in islet hyperplasia and improved glucose tolerance compared to SPF mice. In contrast, we observed higher proportions of effector/memory T cell subsets in blood and liver of high-fat diet AE mice accompanied by the development of nonalcoholic steatohepatitis-like liver pathology. Thus, our data demonstrate the impact of housing conditions on metabolic alterations. Studies in AE mice, in which physiological microbial exposure was restored, could provide a tool for revealing therapeutic targets for immune-based interventions for type 2 diabetes patients.